2001
DOI: 10.1046/j.1365-2206.2001.00185.x
|View full text |Cite
|
Sign up to set email alerts
|

Short breaks for families caring for a disabled child with complex health needs

Abstract: Data from two research studies concerned with disabled children who have complex health needs were analysed in relation to families’ experiences of accessing short breaks (respite) services. Many families experience serious problems finding suitable services which can cater for both their child’s complex health needs and their own need for significant levels of support. This paper highlights which services families were using and the difficulties of obtaining a coherent and consistent package of support. Regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 2 publications
1
22
0
Order By: Relevance
“…Similar findings are reported by parents of children with disabilities (Robinson et al . ) and those whose children received hospice care (Eaton ) and highly valued carers respecting the child's routine. This research identifies all of these components as they relate to respite in children's palliative care in one model.…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings are reported by parents of children with disabilities (Robinson et al . ) and those whose children received hospice care (Eaton ) and highly valued carers respecting the child's routine. This research identifies all of these components as they relate to respite in children's palliative care in one model.…”
Section: Discussionmentioning
confidence: 99%
“…Advances in medical and nursing care augmented by developments in pharmaceutical and health technologies have led to an increasing number of severely disabled children who require complex health care at home (Olsen & Maslin‐Prothero 2001; Robinson et al . 2001; Watson et al .…”
Section: Introductionmentioning
confidence: 99%
“…One study found overnight respite care improved feelings of well-being and reduced depression in mothers of children with severe disabilities (Botuck & Winsberg, 1991). Most respite care research has focused on the frequency of respite care usage (e.g., Damiani, Rosenbaum, Swinton, & Russell, 2004;McConkey & Adams, 2000;Robinson, Jackson, & Townsley, 2001) or descriptions of families who have used respite care services (e.g., Hoare, Harris, Jackson, & Kerley, 1998). The only longitudinal study of overnight respite care benefits for parents of children with developmental disabilities found improvements in psychological distress and parenting stress after 1 month of respite care, with parenting stress levels returning to baseline 6 months later (Mullins, Aniol, Boyd, Page, & Chaney, 2002).…”
mentioning
confidence: 97%
“…Despite the desire and need for respite care services in families who have children with chronic physical conditions, many families have limited access to respite 318 MELTZER AND BENNETT JOHNSON care services for multiple reasons, including a shortage of qualified respite care providers, limited access to respite care resources if a family lives outside of a catchment area, and limited financial resources or reimbursement to pay for respite services (Robinson et al, 2001). A national survey of respite care programs conducted in 2001 estimated that 47% of respite programs have waiting lists, with 52% of programs turning away families.…”
mentioning
confidence: 98%